Evaluation of critical value report of laboratory results based on national quality indicators at Bima general hospital - Pratiwi, Rahma Indah; Pujiyanto, Pujiyanto (Journal of Indonesian Medical Laboratory and Science, 2024)
Background: To improve service quality and patient safety, Bima Regional General Hospital has set quality targets according to the national indicator. One such indicator is the national quality indicator for laboratory services, which aims to achieve a critical laboratory value report of 100%. Objectives: This research aims to evaluate the reporting of laboratory critical values by considering the achievement of predetermined quality indicator targets. Material and Methods: This research was carried out by collecting secondary data using the cross sectional design at Bima Hospital from January 2023 to March 2023 with a total sampling of critical value reports to the clinician or room nurses from all treatment rooms. Achievement of reporting time is calculated based on the percentage of timeliness of reporting critical value results compared to the total of all critical value reporting and is expressed as 'achieved' and 'not achieved'. Results: This research identifies the achievements of reporting that do not meet the target, and several obstacles and challenges that affect the efficiency and effectiveness of reporting. These findings indicate needs for improving coordination, communication and reporting procedures to support better achievement of quality indicator targets. Conclusions: The proposed improvement recommendations can help hospitals optimize the laboratory reporting process, thereby improving the quality of service and overall patient safety.